Flexural behavior and stability of continuous composite beams using NSS and HSS castellated I-sections and slabs of NSC and UHPC - Vinicius Moura de Oliveira; Vinicius Brother dos Santos; Alexandre Rossi; Luciano Rodrigues Ornelas de Lima; Carlos Humberto Martins (Engineering Structures, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Executive summary of the 15th HHT international scientific conference - Freya Droege; Alexandre Guilhem; Nicolas Ricard; Edda Spiekerkoetter; Ruben Hermann; Elisa Rossi; Sabine Bailly; Sophie Dupuis-Girod; Marianne Clancy; Cassi Friday (Angiogenesis, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Evaluation of web post-buckling in high-strength cellular steel and high-strength concrete composite beams: A numerical study - Jonas Yoshihiro Namba; Igor Eduardo da Silva Ribeiro; Haron Cesar Almeida Tavares; Alexandre Rossi; Pablo Augusto Krahl; Carlos Alberto Benedetty Torres; Carlos Humberto Martins (Engineering Structures, 2025)

Steel-UHPC composite castellated beams under hogging bending: Experimental and numerical investigation - Vinicius Moura de Oliveira; Vinicius Brother dos Santos; Alexandre Rossi; André Vitor Benedito; Pablo Augusto Krahl; Carlos Humberto Martins; Flávio de Andrade Silva; Daniel Carlos Taissum Cardoso (Engineering Structures, 2025)

Effects of simulated low-temperature thermal remediation on the microbial community of a tropical creosote contaminated soil - Daniel Di Pace Soares Penna; Valéria Maia Merzel; Juliana Gardenalli de Freitas; Kelly Johanna Hidalgo Martinez; Alexandre Muselli Barbosa; Cristina Rossi Nakayama (Brazilian Journal of Microbiology, 2024)

An assessment on the effects of buffers on the productive, behavioral and metabolic parameters of Holstein dairy cows - Laura Valadão Vieira; Magna Fabrícia Brasil Savela; Natália Machado Rahal; Antônio Amaral Barbosa; Diego Rodrigues Saraiva; Francisco Augusto Burkert Del Pino; Viviane Rohrig Rabassa; Eliza Rossi Komninou; Cássio Cassal Brauner; Diego Langwinski; Alexandre Souza; Marcio Nunes Corrêa (Tropical Animal Health and Production, 2024)

Pervasive transcription of plant organelle genomes: functional noncoding transcriptomes? - Matheus Sanita Lima; Alexandre Rossi Paschoal; Douglas Silva Domingues; David Roy Smith (Trends in Plant Science, 2024)

Artificial neural network modeling of the stability behavior of stainless steel I-beams with sinusoidal web openings - Adriano Silva de Carvalho; Alexandre Rossi; Marcela Moreira da Rocha Almeida; Yasin Onuralp Özkılıç; Carlos Humberto Martins (Engineering Structures, 2024)

Flexural and shear behavior of steel-UHPC composite beams: a review - Carlos Alberto Benedetty; Vinicius Brother dos Santos; Pablo Augusto Krahl; Alexandre Rossi; Flávio de Andrade Silva; Daniel Carlos Taissum Cardoso; Carlos Humberto Martins (Engineering Structures, 2023)

Municipal solid waste management (MSWM) in Brazil: Drivers and best practices towards to circular economy based on European Union and BSI - Perla Calil Pongeluppe Wadhy Rebehy; Alexandre Pereira Salgado Junior; Aldo Roberto Ometto; Diego de Freitas Espinoza; Efigenia Rossi; Juliana Chiaretti Novi (Journal of Cleaner Production, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Embryotoxicity and visual-motor response of functionalized nanostructured hydroxyapatite-based biomaterials in zebrafish (Danio rerio) - Augusto Monteiro de Souza; Heloysa Araujo-Silva; Andréa Machado Costa; Andre Linhares Rossi; Alexandre Malta Rossi; José Mauro Granjeiro; Ana Carolina Luchiari; Silvia Regina Batistuzzo de Medeiros (Chemosphere, 2023)

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

Analysis of the total, annual, and inter-annual hourly mean direct solar normal irradiation - Cícero Manoel dos Santos; Taiza Juliana Rossi; Alexandre Dal Pai; João Francisco Escobedo; Amaury de Souza; Maurício Bruno Prado da Silva; Harry D. Kambezidis (Arabian Journal of Geosciences, 2022)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Interleukin-8 release by endothelial colony-forming cells isolated from idiopathic pulmonary fibrosis patients might contribute to their pathogenicity - Adeline Blandinières; Nicolas Gendron; Nour Bacha; Ivan Bièche; Richard Chocron; Hilario Nunes; Nathalie Nevo; Elisa Rossi; Bruno Crestani; Séverine Lecourt; Sylvie Chevret; Anna Lokajczyk; et al. (Angiogenesis, 2019)

Erratum to: Strontium ranelate changes the composition and crystal structure of the biological bone-like apatite produced in osteoblast cell cultures - William Querido; Andrea P. C. Campos; Erlon H. Martins Ferreira; Rosane A. S. San Gil; Alexandre M. Rossi; Marcos Farina (Cell and Tissue Research, 2014)

Strontium ranelate changes the composition and crystal structure of the biological bone-like apatite produced in osteoblast cell cultures - William Querido; Andrea P. C. Campos; Erlon H. Martins Ferreira; Rosane A. S. San Gil; Alexandre M. Rossi; Marcos Farina (Cell and Tissue Research, 2014)